Wideband and flat-gain amplifier based on high concentration erbium-doped fibres in parallel double-pass configuration - Hamida, Belal Ahmed; Cheng, X.S.; Harun , Sulaiman Wadi; Naji, Ahmed Wathik; Arof, Hamzah; Al-Khateeb, Wajdi Fawzi Mohammed; Khan, Sheroz; Ahmad, Harith (Kvantovaya Elektronika and Turpion Ltd, 2012)
A wideband and flat gain erbium-doped fibre amplifier (EDFA) is demonstrated using a hybrid gain medium of a zirconiabased erbium-doped fibre (Zr-EDF) and a high concentration erbium-doped fibre (EDF). The amplifier has two stages comprising a 2-m-long ZEDF and 9-m-long EDF optimised for C- and L-band operations, respectively, in a double-pass parallel configuration. A chirp fibre Bragg grating (CFBG) is used in both stages to ensure double propagation of the signal and thus to increase the attainable gain in both C- and L-band regions. At an input signal power of 0 dBm, a flat gain of 15 dB is achieved with a gain variation of less than 0.5 dB within a wide wavelength range from 1530 to 1605 nm. The corresponding noise figure varies from 6.2 to 10.8 dB within this wavelength region.